2012
DOI: 10.3233/wor-2012-0135-55
|View full text |Cite
|
Sign up to set email alerts
|

Contributions from the activity analysis to the products development project: case study based on a project of innovation and comfort in aircraft’s cabins

Abstract: Comfort is an issue that has gained relevance within the aeronautical industry due to the necessity of manufacturers and airline companies of differentiating themselves in a market that has become more and more competitive each day. This study's aim is to analyze the comfort/discomfort of passengers, based on the analysis of the activities performed in the aircrafts' cabin during real flights, in order to create ergonomics requirements and a methodology of comfort analysis. The study has been performed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…() stated that passengers’ activities would vary depending on flight duration. Greghi, Rossi, Souza, and Menegon () compared the space occupied by passengers performing different activities with the existing cabin space using a methodology called calculation of posture envelopes . The results indicated that the existing cabin space, especially in the economy class, severely limited passengers’ activities and created some difficulties for passengers’ body movements, which was the main reason passengers felt discomfort in performing certain activities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…() stated that passengers’ activities would vary depending on flight duration. Greghi, Rossi, Souza, and Menegon () compared the space occupied by passengers performing different activities with the existing cabin space using a methodology called calculation of posture envelopes . The results indicated that the existing cabin space, especially in the economy class, severely limited passengers’ activities and created some difficulties for passengers’ body movements, which was the main reason passengers felt discomfort in performing certain activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Objective methods aim to collect and analyze objective data using different devices, such as pressure mats, electroencephalographs, and electromyographs. The comfort levels of subjects can be obtained by analyzing their movements and posture (Apostolico, Cappetti, D'Oria, Naddeo, & Sestri, ; Brenner, ; Greghi et al., ; Lueder, ; Rossi et al., ), pressure measurements (Fujimaki & Mitsuya, ; Groenesteijn et al., ; Vergara & Page, ), electromyography (EMG) (Rodrigues‐de‐Paula‐Goulart & Valls‐Solé, ), and so forth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to design a seat pan and backrest of an aircraft seat based on the human contour, first the most frequently performed activities in aircraft seats were determined by interviewing three experienced long-haul frequent flyers (age 58-64, flying for both business and leisure). These activities were compared and confirmed by literature [10,11]. Second, the preferred inclination angles corresponding with the determined activities were established.…”
Section: Methodsmentioning
confidence: 75%
“…O protocolo proposto para esta etapa da pesquisa sugere a utilização de medição contínua de pressão em conjunto com outras técnicas, como observação, relato pós-experimento e filmagem para avaliar o conforto e o desconforto percebidos pelo passageiro durante a realização das atividades de repousar e ler. As atividades de repousar e ler foram escolhidas pelo alto grau de dificuldade de realização, segundo estudos na literatura (Oborne, 1978, Greghi et al, 2012.…”
Section: Imersãounclassified